An examination of cross-cultural differences in e-service quality, e-satisfaction and e-marketing success: Korean vs. American portal sites. (2016) - Fan, Qingji; Kim, Hye-Ran; Lee, Jeoung Yul
The purpose of this study is to examine e-service quality, e-satisfaction and e-WOM performance as measures of e-marketing success and identify whether or not cultural differences influence e-marketing success between South Korea and the USA. Especially, our focus is on customers of portal sites, i.e., Naver and Google (the largest portals in the two countries). A cross-culture survey was conducted and 250 Koreans and 300 Americans responses were collected by two commercial research institutes in Korea and the USA, respectively. The four dimensions of e-service quality and e-WOM performance were suggested as antecedents and output, respectively, as e-marketing success by a few analyses. Noticeably, we found that there are differences in influences of credibility and responsiveness on e-satisfaction between the Korean and American portal site customers but there are no significant differences in influences of the other variables such as contents attractiveness and entertainment. This suggests that the differences lead to better understanding of cultural influences on e-marketing and provide practical implications to internet companies offering services internationally.